Towards a better understanding of medical students’ mentorship needs: a self-determination theory perspective - Neufeld, Adam; Hughton, Bryden; Muhammadzai, Javeria; McKague, Meredith; Malin, Greg (Canadian Medical Education Journal, 2021)
Introduction: Mentorship programs are ubiquitous in medical education. However, few emphasize equal development for learners and mentors, or incorporate clinical skills, which may be important for promoting medical students’ self-determination. Central to this consideration are the three basic psychological needs for autonomy, competence, and relatedness, described by Self-Determination Theory (SDT). Grounded in SDT, this study assesses the extent that meeting these needs, in a near-peer mentoring program, impacts learners’ and mentors’ motivation and perceived competence about learning and teaching of clinical knowledge, respectively. Methods: Medical students from the University of Saskatchewan, who participated in its near-peer mentoring program (PULSE: Peers United in Leadership & Skills Enhancement), were invited to complete an anonymous survey. Regression was used to determine how the program’s learning climate impacted learners’ and mentors’ psychological need satisfaction and perceived competence within their mentorship role. Results: Learners and mentors both rated PULSE as highly needs-satisfying. In turn, this was associated with greater perceived competence about learning and teaching of the material. Conclusions: Findings from this study suggest that mentoring programs in medical education, which support learners’ basic psychological needs, may promote their motivation and perceived competence—both about learning and also teaching of clinical skills. The implications of these results are discussed from an SDT perspective, with respect to mentoring programs in medical education.